Efektivitas Komposit dalam Memperkuat Rompi Anti Peluru - Hertanto, Theofillus Lisa Okta; Aritonang, Sovian; Murniati, Riri (Fakultas Teknik UMSU, 2024)
This research examines the effectiveness of bulletproof vests made with composite materials, focusing on carbon fiber. The study finds that the thickness of the carbon fiber and the HGM plastic coating in the vest are crucial factors in enhancing protection against bullet penetration. In some instances, thicker composite materials offer better defense. Furthermore, the use of composites allows for lightweight vests, reducing the physical strain on the wearer. These findings have significant implications for the development of personal protective equipment in various sectors, such as the military, law enforcement, and industries like construction. Enhancing the efficacy of bulletproof vests through the integration of composite materials is a vital stride in enhancing the safety of individuals encountering potential bullet threats.